Perancangan Ulang Interior Badan Arsip dan Perpustakaan Propinsi Jawa Tengah - Melani, Christine (Intra, 2013)
From the survey that was held by KPPOD on 2009, it was discovered that Semarang ranked 13th place among 15 metropolitan cities in Indonesia. This situation inspires city officials to do an all-around development. The key for a successful development in a region is the human resources, but in Indonesia where not everyone could afford to have a proper education it became difficult to attain this goal. In this situation library held an important role, because the main principle of a library is the equity to access information for everyone, no matter what gender, nationality, age, education and status they have. But, Central Java Library and Archive as the main library in Semarang still has some issues left unresolved. This redesign aim to analyze all the problems thatâs happening on the building and looking for the right solution for it, while on the other hand keep maintaining all the roles that this building held, whether as Public Library, Regional Library, or as Government Building, to be fulfilled. Those roles demanded a building which accessible to everyone, facilitate all kinds of visitors, prioritizing the health of buildingâs users, preserving the environment, also could represent the identity of Central Java at the same time.